A Meta-Analysis of Avian Egg Traits Cueing Egg-Rejection Defenses Against Brood Parasitism - Samaš, Peter; Hauber, Mark E.; Honza, Marcel (Frontiers in Ecology and Evolution, 2021)
The capability of hosts to reject the odd egg from their nest is one of the key defenses against avian brood parasitism. Considerable research effort has been devoted to exploring which phenotypic traits of eggshells facilitate to cue the recognition of the parasitic egg. Here we have reviewed studies addressing salient egg traits involved in the rejection of foreign eggs and used a formal meta-analysis to quantify their relative importance. Hosts appear to rely to a large extent on eggshell color traits, followed by maculation patterns. Hosts respond with similar rates of egg rejection to natural versus model eggs and when breeding in both closed and open nests. Analyses of experiments on hosts of Cuculus and Molothrus parasites, the two best studied brood parasitic lineages with different co-evolutionary histories, yield similar conclusions. We also identify several poorly studied potential egg recognition cues, such as odor or weight, and recommend exploring even the visual traits in more detail, including chromatic and achromatic contrasts or experimentally manipulated egg maculation characteristics. Recent technological and sensory ecological advances open many new research avenues to experimentally examine the role of diverse egg characteristics in antiparasite defenses.